Coffee, Space, and Power: The Unique Relationship between Coffee-Drinking Culture and Political Processes in the Context of Elections - Alieffayyadh, Uti Muhammad; M, Gilbert; Yeti, Krister; Ardila, Maria; Zhan, Fuzy Firda (INDEF - Institute for Development of Economics and Finance, 2025)
Coffee, as a global commodity, is not merely an agricultural product but also a site of political and economic contestation involving land use, resource control, and power relations. This study examines the intricate relationship between coffee-drinking culture and electoral processes. Employing a literature-based approach, data were gathered from journal articles, books, news reports, and other relevant publications. The study finds that coffee culture is not merely a component of lifestyle but also shapes deliberative spaces that influence political awareness and electoral behaviour. Coffee shops serve as informal arenas where political issues are openly discussed, fostering social networks that play a significant role in shaping public opinion. The most significant finding of this study is that coffee shops function as hybrid socio-political spaces where everyday social interaction, digital communication, and informal campaigning intersect, enabling political actors to engage voters through subtle and personalised approaches. The literature further indicates that the intensity of social interaction within these spaces can strengthen citizens’ engagement in democratic processes, heighten interest in policy issues, and, in some cases, directly influence political choices. Thus, this study underscores that coffee culture should not be viewed solely as an economic or lifestyle phenomenon but also as a critical medium in contemporary political dynamics. Keywords: Coffee, Spatial Politics, Political Economy JEL: A11, A13